Impact of Contralateral Symmetry Procedures on Long-Term Patient-Reported Outcomes following Unilateral Prosthetic Breast Reconstruction - Razdan, Shantanu N.; Panchal, Hina; Albornoz, Claudia R.; Pusic, Andrea L.; McCarthy, Colleen C.; Cordeiro, Peter G.; Disa, Joseph J.; Mehrara, Babak J.; Matros, Evan (Journal of Reconstructive Microsurgery, 2019)
Background One aim of unilateral postmastectomy breast reconstruction (BR) is to restore symmetry with the contralateral breast. As such, unilateral prosthetic reconstruction often requires a contralateral symmetry procedure (CSP). There is sparse literature on the impact of CSPs on long-term patient-reported outcomes (PROs) such as satisfaction and health-related quality of life (HRQoL). This study aims to describe PROs following CSPs, using a validated PRO tool, BREAST-Q. The hypothesis is that CSPs are associated with greater patient-reported satisfaction and HRQoL.Methods This study is a single institutional analysis of prospectively collected BREAST-Q scores of patients who underwent unilateral prosthetic BR during 2011 to 2015. Women 18 years and older with BREAST-Q scores measured ≥ 9months after BR with or without CSP(s) at the time of expander replacement were included. Patients were classified into four subcohorts: augmentation, mastopexy, reduction, and no symmetry procedure (controls). Sociodemographic, clinical characteristics, and BREAST-Q scores were analyzed. Multivariable linear regression was performed.Results Of 553 patients, 67 (12%) underwent contralateral augmentation, 68 (12%) mastopexy, 93(17%) reduction, and 325 (59%) were controls. Mean follow-up time was 52 months. Satisfaction with breast and outcomes were higher in the augmentation compared with the control groups (p = 0.01). On multivariable analysis, augmentation remained an independent predictor of satisfaction with breast (p = 0.04). Physical well-being scores were lower for contralateral mastopexy and reduction compared with the controls with a trend toward statistical significance on multivariable models. Psychological and sexual well-being was similar across groups.Conclusion Prosthetic reconstruction with contralateral breast augmentation was associated with greater satisfaction with breast and reconstructive outcome. In contrast, breast reduction and mastopexy procedures demonstrated equivalent satisfaction with breasts compared with controls but may be associated with lower physical well-being. Such information can be used to improve the shared decision-making process for women who choose unilateral prosthetic BR.
Keywords: BREAST-Q; contralateral symmetry procedure; unilateral prosthetic breast reconstruction